A windowed carbon nanotube membrane for CO2/CH4 gas mixture penetration separation: insights from theoretical calculation. Issue 26 (6th June 2022) - Miao, Feng; Jiang, Hao
Abstract : Final snapshot of the CO2 /CH4 gas mixture separating through the windowed carbon nanotube membrane. Abstract : A new class of species-permselective molecular sieves with functionalized nanowindows has been prepared by modifying the armchair single-walled carbon nanotubes (SWNTs) of a pillared graphene membrane, namely windowed carbon nanotube membrane. The mechanism and characteristics of the windowed carbon nanotube membrane for the selective separation of the CO2 /CH4 gas mixture are comprehensively and deeply studied. Selective gas separation has a great dependence not only on the interaction of the gas adsorbing on the graphene membrane and inside the CNT channel but also with the energy barrier for the gas diffusing through the nanowindow. In all the functional nanowindows investigated, CH4 is completely rejected by the N/F-modified nanowindows while maintaining extremely high CO2 permeability. The CO2 permeance of the nanowindows is as high as 10 9 GPU. It emerged that these windowed carbon nanotube membranes are efficient species-selective molecular sieves possessing excellent CO2 /CH4 selectivity and brilliant CO2 capture capability.